A Laboratory-Based Investigation of Links between Maternal Posttraumatic Stress Symptoms and Adolescent Offspring Anxiety. (2nd January 2022) - Bilsky, Sarah; Dickerson, Laura; Mischel, Emily; Mahan, Rebecca; Leen-Feldner, Ellen
SYNOPSIS: Objective . Maternal symptoms of posttraumatic stress are linked to problematic offspring outcomes, including internalizing problems, general behavioral problems, and altered psychobiological functioning. Maternal posttraumatic stress symptoms among trauma-exposed mothers as they relate to offspring functioning has not been evaluated, and laboratory-based affect elicitation procedures have not been used in this context. Design . Self-report of trauma-relevant symptoms in 40 mothers and their adolescents' self-report indices of adolescent anxiety symptoms were obtained. Adolescents were also administered a laboratory-based induction of socially relevant anxious arousal, and maternal and adolescent anxiety in response to the task were recorded. Results . Maternal posttraumatic avoidance symptoms were associated with questionnaire- and laboratory-based indicators of adolescent anxiety. Conclusions . Maternal posttraumatic avoidance symptoms are associated with offspring anxiety; therefore, providers working with mothers with posttraumatic avoidance should consider screening adolescent offspring for anxiety symptoms.